Socio-environmental analysis of the rural zone of Espírito Santo do Dourado/MG: a perspective for future integration policies - Andrade, Marielle Rezende de; Ávila, Fábio Geraldo; Junior, Roosevelt Heldt Junior Heldt; Santos, Mireile Reis dos (Revista Agrogeoambiental, 2021)
Issues referring to environmental conservation and diagnosis of rural zones are still scarce topics inside public policies and this aspect still requires greater attention. That being, the goal of this research was to present a diagnosis of the rural area of a small city in the South of the Minas Gerais State, with typical agricultural characteristics and large availability of water in order to verify possible socio-environmental inconsistencies. The data was gathered from secondary information of the federal, state, and town public databases, besides face-to-face questionnaires, rapid assessment protocols and high-definition satellite mapping of land use for the last few years. It was possible to assess that conservation actions and Permanent Preservation Areas (APPs) are reduced and that interviewed people present limited knowledge about public policies of family farming stimulation. As per rural basic sanitation, practical action by local governments must be prioritized. The conclusion of this diagnosis is to suggest that further investments should be prioritized to assist social and environmental segments.